Experimental and numerical investigation on part thicknesses effects in tailor welded blank process - Anas Basri, Musthafa (2013)
Tailor welded blank (TWB) is increasingly popular in producing sheet metal components especially for automotive industry. TWBs is employed by using dissimilar material welding which is mainly affected blank thickness and type of material used. This study is focused on the part thickness effects using experimental and numerical method. Thickness of tailor welded sheets plays an important role in sheet metal forming since fracture, wrinkling and weak spots are strongly influenced by material behaviour. In this study, simple heat transfer testing equipment is fabricated to conduct heat transfer experiment. A numerical and experimental study was carried out to investigate the heat transfer characteristic for different thickness of common used type of TWB material. The investigated thicknesses of aluminum 1100 are 1, 2 and 3 mm. Low heat capacity laser is used to measure the temperature distribution in experiment and used to validate FE model. A finite element model (2D) of aluminum 1100 is applied to simulate static heat distribution inside the material for different part thicknesses, heating position and amount of heat. The results shown that the heating region for thicker plate for combination 3 mm with 1 mm is 60 % wider compare to thinner plate with 40 %. Different combination of material thickness requires different heating positions and increasing the thickness of the material is increases the use of heat flux